Drug Repurposing for the Treatment of Acute Myeloid Leukemia - Andresen, Vibeke; Gjertsen, Bjørn T. (Frontiers in Medicine, 2017)
Acute myeloid leukemia (AML) is a heterogeneous disease characterized by the accumulation of immature myeloid progenitor cells in the bone marrow, compromising of normal blood cell production and ultimately resulting in bone marrow failure. With a 20% overall survival rate at 5 years and 50% in the 18- to 65-year-old age group, new medicines are needed. It is proposed that development of repurposed drugs may be a part of the new therapy needed. AML is subdivided into recurrent molecular entities based on molecular genetics increasingly accessible for precision medicine. Novel therapy developments form a basis for novel multimodality therapy and include liposomal daunorubicin/cytarabine, broad or FLT3-specific tyrosine kinase inhibitors, Bcl-2 family inhibitors, selective inhibitors of nuclear export, metabolic inhibitors, and demethylating agents. The use of non-transplant immunotherapy is in early development in AML with the exceptional re-approval of a toxin-conjugated anti-CD33. However, the full potential of small molecule inhibitors and modalities like immunological checkpoint inhibitors, immunostimulatory small molecules, and CAR-T cell therapy is unknown. Some novel therapeutics will certainly benefit AML patient subgroups; however, due to high cost, more affordable alternatives are needed globally. Also the heterogeneity of AML will likely demand a broader repertoire of therapeutic molecules. Drug repurposing or repositioning represent a source for potential therapeutics with well-known toxicity profiles and reasonable prices. This implies that biomarkers of response need to accompany the development of antileukemic therapies for sharply defined patient subgroups. We will illustrate repurposing in AML with selected examples and discuss some experimental and regulatory limitations that may obstruct this development.